How To Make Xiao Long Bao Fusion With Indonesia Cuisine - Nyoman Damien Horn; Jonathan Oei; Carven Carven; Juliana Juliana (Journal of Community Service and Engagement, 2022)
This paper is about the implementation of the idea of Food Fusion in the field in the form of Community Service for a village named Curug Wetan. The purpose of the paper is to essentially document the efforts of the team as the task is being done and the methods that have been implemented by the team to make sure that the operation runs smoothly. This paper is also to convey the feelings of the team on the products that have been made but will mostly focus on the operations of the event that took place rather than the products. The event was to show the people of Curug Wetan village the methods in making two out of the four types of Xiao Long Bao which were the Soto Betawi variant and the Soto Lamongan. The reason being is that those two products have been some of the better performing of the four when it came to the testing from Panelists. As Curug Wetan seemed to have trouble advertising their brands outside of the village (Jeklin, 2016) so the team made the decision that the creation of a new variant of an existing and established food can be a driving force for people to start something new and to expand their businesses even if it’s a tiny bit.